Optimization of coagulation with PFS-PDADMAC composite coagulants using the response surface methodology experimental design technique - Tshukudu, Tiroyaone (Water environment research : a research publication of the Water Environment Federation, 2013)
In this study, two composite coagulants, PFPD1, and PFPD2, were prepared and studied with the inorganic polymer coagulant PFS. A response surface design was used to investigate the effect that changes in the level of coagulant dose and coagulation pH have on residual turbidity and TOC. In addition, the optimum combinations of dose and pH, that yield the lowest residual turbidity and TOC, were determined. The results revealed that the optimum conditions for the three coagulants were a dosage of 204 mg/L and pH of 8.06 for PFS; a dosage of 179 mg/L and pH of 7.99 for PFPD1; and a dosage of 112 mg/L and pH of 7.65 for PFPD2. The models showed that for residual turbidity, the effectiveness of the coagulants in decreasing order was PFS>PFPD1 > PFPD2, while for residual TOC, the order was PFPD2 > PFPD1 > PFS. The verification experiments demonstrated that a RSM approach was appropriate for optimizing the coagulation-flocculation process